An overview of chromatin modifications. Issue 2 (22nd November 2012) - Fick, Robert J.; Trievel, Raymond C.; Trievel, Ray
Abstract The last 15 years have witnessed tremendous progress in elucidating the roles of chromatin modifications in transcription regulation, DNA repair, replication, recombination, and other genomic processes. In this issue of Biopolymers, a series of reviews will summarize recent advances in our understanding of chromatin modifying enzymes and explore unresolved questions with respect to their regulation and functions in gene expression and other nuclear processes. © 2012 Wiley Periodicals, Inc. Biopolymers 99: 95–97, 2013.